Вапняковий нанопланктон з келовейських відкладів району Канівських дислокацій - Матлай, Л.М. (Інститут геологічних наук НАН України, 2009)
Впервые изучен известковый наннопланктон в келловейских отложениях Каневских дислокаций. Определена стратиграфическая принадлежность ассоциаций наннопланктона. По наличию вида Stephanolithion bigotii maximum D e f l a n d r e установлен верхний келловей. Calcareous nannofossils have been investigated аt first in Callovian deposits of Kanev`s dislocation region. The stratigraphic implements of this nannofossil`s associations have been istablished according to the Stephanolithion`s species presents.